O Papel do Estado na promoção do Desenvolvimento Nacional: a utilização do instrumento do planejamento na expansão da oferta energética - Dantas, Daniel Ramos (2011)
The progress of a nation is closely linked to the energy supply that it has to develop its economic capabilities. The dependence of contemporary society for energy requires the continued expansion of the use of renewable energy, and implies coordinated action of the Democratic State in the delimitation of the best ways to make full use of energy. In periods of rapid development, countries need an increment of energy supplies superior to those of periods of regular economic growth. Energy demand generated by the condition of Brazil as an emerging country reveals the need for orderly expansion of energy supply. In reverse, lack of energy planning effectively paralyzes a country and generates incalculable losses in national socioeconomic development. The Brazilian Constitution abandoned the notion of development tied to the simple increase in the gross domestic product. The respect for the environment, sovereignty, national development, and especially the constant and growing supply of energy, promotes the advancement of national economic agents, and quenches the simple accounting increase in energy supply. Constitutional principles condition the rational use of energy potentials, in ensuring adequate supply of energy for the entire national territory. The Brazilian Ministry of Mines and Energy, through its agencies, government offices and companies, establishes and formulates policies and guidelines for energy in Brazil, playing an important role in national energy planning. National development is enhanced by the good performance of the state agencies responsible for planning the energy sector